2024
DOI: 10.1039/d4dt00296b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of various reducing agents on Cu nanocluster synthesis

Sourav Biswas,
Yuichi Negishi

Abstract: The synthesis of copper (Cu) nanoclusters (NCs) has experienced significant advancements in recent years. Despite the exploration of metal NCs dating back almost two decades, challenges specific to Cu NC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…Exclusive examination of these reactions reveals a spectrum ranging from intricate solvochemical processes to cutting-edge electrocatalysis. Their meticulously crafted structural architecture and distinctive surface properties, combined with the reduction potential of Cu atoms, empower them to catalyze reactions with exceptional efficiency and selectivity in various chemical contexts. Nevertheless, it has been observed that numerous factors influence the control of their structural architecture and surface characteristics. Alterations in their structural configuration also lead to specific changes in their photophysical properties, a widely discussed aspect attributed to their atomic confinement. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusive examination of these reactions reveals a spectrum ranging from intricate solvochemical processes to cutting-edge electrocatalysis. Their meticulously crafted structural architecture and distinctive surface properties, combined with the reduction potential of Cu atoms, empower them to catalyze reactions with exceptional efficiency and selectivity in various chemical contexts. Nevertheless, it has been observed that numerous factors influence the control of their structural architecture and surface characteristics. Alterations in their structural configuration also lead to specific changes in their photophysical properties, a widely discussed aspect attributed to their atomic confinement. , …”
Section: Introductionmentioning
confidence: 99%
“…Since the synthesis of Cu NCs, the predominant methodology has been the modified Burst method, renowned for its efficacy. This approach necessitates a potent reducing agent such as [BH 4 ] − , utilized in abundance. , However, the utilization of such reducing agents engenders the incorporation of numerous hydrides within the structure of the NCs. , Consequently, when these NCs are employed in various applications, the presence of hydrides can significantly impact their performance and functionality. Moreover, the occasional scarcity of hydride-free Cu NCs constrains the comparative analysis pathway overall.…”
Section: Introductionmentioning
confidence: 99%